Creative processes in visual arts in education: a conceptual framework - Swanzy-Impraim, Enock (Creativity Studies, 2025)
The diversity and uniqueness of individuals and the multifaceted nature of creativity necessitate new models in various domains. This study reviewed previous studies and models of the creative process and presented a combined model (Swanzy-Impraim panoramic creative process model) of the creative process applicable to the visual arts in education and other artist-expressive domains. It positions the creative process in seven phases: (1) immersion, (2) problem/task identification, (3) ideation, (4) production, (5) outcome, (6) evaluation, and (7) responses. This conceptual paper explores creativity as a concept and its significance in the artists’ expressive domain, reviews and maps creative process models, and develops a comprehensive Swanzy-Impraim panoramic creative process model. The model can support the creativity agenda in education and creativity enactment within the arts.